Suppose that f is an exponential function such that f(x) = 4 • 2^x Which answer shows that this exponential function grows by equal factors over equal intervals?

O f(4) • f(3) = f(7) • f(6)

O f(4) + f(3) = f(7) + f(6)

O f(4) divide f(3) = f(7) divide f(6)

O f(4) – f(3) = f(7) – f(6)

B.f(4)=22

Step-by-step explanation:

To find f(4), plug in x = 4 into the function

f(4) = 3(4) +10 = 12 + 10 = 22

The correct answer is A

Step-by-step explanation:

Exponential functions grow by equal factors over equal intervals because the change in x is always the same as the exponent of the quotient of the values of y.

Answer with Step-by-step explanation:

We are given that:

f(x)=9x

A)f(4) f(1) = f(8) f(5)

f(4)f(1)=9×4×9×1=324

f(8)f(5)=9×8×9×5=3240

Hence, this option is incorrect

B)f(4)·f(1) = f(8)·f(5)

f(4)f(1)=324

f(8)f(5)=3240

Hence, this option is incorrect

C)f(4) − f(1) = f(8) − f(5)

f(4)-f(1)=9×4-9=27

f(8) − f(5)=9×8-9×5=27

Hence, this option is correct

D)f(4) − f(1) = f(−4) − f(−1)

f(4) − f(1)=9×4-9=27

f(−4) − f(−1)=9×(-4)+9=-27

Hence, this option is incorrect

Correct option is:

C)f(4) − f(1) = f(8) − f(5)

Option (1)

Step-by-step explanation:

Two functions 'f' and 'g' have been graphed in the picture attached.

Both the functions will be equal at the points where the values of these functions are equal.

Those points are the point of intersection of both the functions on the given graph.

At x = -4,

f(-4) = g(-4) = 4

At x = 0,

f(0) = g(0) = 4

Therefore, Option (1) will be the answer.

Hi ofmr me heike ong susie didn’t heiße omg how song

f(4) = g(4) and f(0) = g(0)

Step-by-step explanation:

In order for f(x) = g(x), the value of x must be the same in both functions:

f(4) = g(4) . . . corresponds to x=4

f(0) = g(0) . . . corresponds to x=0

The graph is not shown here, so we cannot say if these are the appropriate solutions. We can only say that the other choices are not.

f(x) = g(x) if ...

f(4) = g(4) and f(0) = g(0)

__

Something like f(0) = g(4) is useless for finding solutions to f(x) = g(x).

Aline graph should be used

B

Step-by-step explanation:

f(x) = 3x² - 5x + 10

f(4) = 3*4² - 5*4 +10

= 3*16 - 20 +10

= 48 - 20 + 10

f(4) = 38

answer: the two figures are congruent.

step-by-step explanation: they're congruent because figure efgh is reflected across the x and y axis but it was also rotated.

hope it !

[tex](02.05 mc) determine if the two figures are congruent and explain your answer.[/tex]

????????????????????????????????????????????????????????????????????????????????????????????????????????????????????????????????????????????????????????????????????????????????????????????????????????????????????????????????????????????????????????????????????????????????????????????????????????????????????????????????????????????????????????????????????????????????????????????????????????????????????????????????????????????????????????????????????????????????????????????????????????????????????????????????????????????????????????????????????????????????????????????????????????????????????????????????????????????????????????????????????????????????????????????????????????????????????????????????????????????????????????????????????????????????????????????????????????????????????????

[tex]Evaluate the function when x = 4 1. f(4) = 2(4) - 5 = 3 2. f(4) = 2(4) - 5 = -1 3. f(4) = 1/2(4) +[/tex]

[tex]\large\boxed{B.\ f(4)=22}[/tex]

Step-by-step explanation:

[tex]f(x)=3x+10\\\\f(4)-\text{put x = 4 to the equation of the function}\\\\f(4)=3(4)+10=12+10=22[/tex]

C

Explanation: it’s the longest one